Armazenamento de sementes de sorgo, colhidas com diferentes graus de umidade e submetidas a tempos de espera para secagem - Souza, Glaucia de Fatima Moreira Vieira e (2006)
The effect of storage in a climatized environment on the physiologic quality of hybrid AG 1018 sorghum (Sorghum bicolor L. Moench) seeds harvested with different moisture contents and subjected to delay times before drying was studied. The seeds used were collected in a commercial seed production field of Monsanto Brasil Ltd., in Uberlândia-MG, in the cropping season 2002/2003. The samples were placed in multi-layer paper bags, stored in a climatized warehouse (temperature 10ºC and relative humidity 50%) at the processing unit of Monsanto Brasil Ltd., in Uberlândia-MG. The experimental design was randomized blocks with split plots on time. In the experimental unit a 4x4 factorial was analyzed, consisting of seed samples harvested with four moisture contents (20%, 18%, 14% and 11%) and subjected to four delay times before drying started (6, 12, 18 and 24 hours), while four storage times were analyzed in the split plots (beginning of storage, 120, 300 and 480 days), on September 2003, January 2004, July2004 and January 2005, respectively. Changes on moisture, weight of one thousand seeds and on seed physiological quality were studied using germination and cold tests. It can be concluded that: a) the moisture contents of the sorghum seeds increased with storage time; b) the weight of one thousand seeds changed during storage as a function of programmed harvest moisture and delay time for beginning drying; c) seed physiologic quality decreased with programmed harvest moisture and storage time; d) according to commercialization standards, although significantly reduced, seed germination after 480 days of storage was still satisfactory.